THE EFFECT OF PORPHYROMONAS GINGIVALIS INFECTION ON MENOPAUSE TO THE MECHANICAL STRENGTH OF THE MANDIBLE AND FEMUR - Agustin Wulan Suci Dharmayanti; Roedy Budirahardjo; Bangun Febrianto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Menopause is physiological condition signed estrogen deficiency. Porphyromonas gingivalis (Pg), Gram-negative bacteria, and the products might induce estrogen deficiency. Estrogen is a sex steroid hormone played an essential role in bone remodeling. The purpose of this study was to determine the effect of Pg infection to menopause on the mechanical strength of the mandible and the femur. Following this study, we suggested that there were efforts to improve the health of oral, reproductive, and bones, particularly improving women's quality of life. This study was an experimental laboratory by post-test only control group design.Method: This study used female Wistar rats (Rattus norvegicus) divided into four groups. The groups were the control group (K), ovariectomy (OVX), Pg- induced (PG), and Pg-induced ovariectomy (OPG). OVX indicated ovarian dysfunction due to physiological processes. PG indicated experimental animals infected with Pg bacteria which was suspected of causing ovarian dysfunction. OPG indicated that experimental animals infected with Pg bacteria were in a state of menopause. A three-point bending test analyzed bone strength. Result: The results showed that the average mechanical strength of the mandibular bone in the control group and the treatment group had a significant difference (p<0.05), but there was no significant difference between the strength of the femur bone between the control group and the PG group (p>0.05).Conclusion: Pg infection in menopause triggered a decrease in the mechanical strength of bones, especially the mandibular bone.